The Oxford-Hachette French dictionary French-English, English-French - Corréard, Marie-Hélène; Grundy, Valerie; Ormal-Grenon, Jean-Benoit; Rollin, Nicholas (Oxford University Press, 2007)
A book that lists French language words and gives their equivalent in English, and English language words with their equivalent in French.